AR 2017
DOI: 10.21873/anticanres.12011
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of PET/CT in the Initial Staging of Hodgkin Lymphoma: Experience Outside Clinical Trials

Abstract: Baseline PET/CT findings may lead to treatment modification in <15% of patients with HL without a significant impact on outcome. Certain PET/CT parameters have potent prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Despite treatment, about 20% of HL patients still relapse (1). 18 F-Fluorodeoxyglucose ( 18 F-FDG) Positron Emission Tomography (PET) coupled with Computed Tomography (CT) plays a central role in HL patients management, whether in staging or response assessment settings (1).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite treatment, about 20% of HL patients still relapse (1). 18 F-Fluorodeoxyglucose ( 18 F-FDG) Positron Emission Tomography (PET) coupled with Computed Tomography (CT) plays a central role in HL patients management, whether in staging or response assessment settings (1).…”
Section: Introductionmentioning
confidence: 99%
“…The drawbacks of TMTV calculation (results depending on the segmentation method (9), time required for delineation (10), difficulty in evaluating bone involvement) led to ponder other prognostic markers, such as healthy organ 18 F-FDG uptake. In 2010, Hanaoka et al (11) reported an inverse correlation between cerebellar uptake and total lesion glycolysis (TLG) in a population with aggressive lymphoma.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations